THE DEVELOPMENT OF THE PROFESSIONAL IDENTITY OF MATHEMATICS TEACHERS IN THE CONTEXT OF DIGITAL CULTURE - dos Santos, André Gomes; de Aguiar, Heraldo Márcio; Schimiguel, Juliano (Seven Editora, 2026)
This article investigates the process of professional identity development among mathematics teachers in contemporary times, marked by the growing influence of digital culture. It analyzes how the integration of digital technologies into mathematics teaching and learning impacts how these professionals perceive themselves, act, and construct their pedagogical identity. The research explores the tensions, challenges, and opportunities that emerge from this relationship between the teaching profession and the digital context, considering changes in teaching practices, interactions with students, and the perception of one's own role as a mathematics educator. Based on a comprehensive literature review and practical examples, the implications for initial and continuing education for mathematics teachers are discussed, aiming to strengthen resilient professional identities adapted to the challenges of the 21st century.